Effect of heat treatment in the structure and microstructure of Ti-15Zr-XMo alloys - Correa, D. R.N. [UNESP]; Kuroda, P. A.B. [UNESP]; Lourenço, M. L. [UNESP]; Grandini, C. R. [UNESP] (Trans Tech Publications, 2015)
Titanium alloys present favorable properties to industry applications that depend on their composition and microstructure. Adding alloy elements and thermomechanical treatments can change the microstructure of titanium alloys. In this paper, Ti-15Zr alloys with different molybdenum quantities were prepared and hot-rolled, having been previously subjected to homogenizing heat treatment. The results showed that the microstructure of the alloys was sensible to heat treatment, in accordance with the theoretical prediction from the molecular orbital method.
Keywords: Heat treatment; Microstructure; Ti-based alloys